General and Selective C‐3 Alkylation of Indoles with Primary Alcohols by a Reusable Pt Nanocluster Catalyst. Issue 43 (20th September 2013) - Siddiki, S. M. A. Hakim; Kon, Kenichi; Shimizu, Ken‐ichi
<x xml:space="preserve">Abstract</x> The platinum rule: Heterogeneous, additive‐free C‐3 selective alkylation of indoles by aliphatic and aromatic alcohols proceeded under transfer hydrogenation conditions with the reusable Pt/θ‐Al2O3 catalyst (see scheme; TON=turnover number).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>